Integrated Use of Constructed Wetlands for Livestock Wastewater Treatment and Fodder Production - Ngo, Thuy Diem Trang (2004)
Constructed wetlands (CW) are widely used to treat wastewater (WW) because of its high efficiency for removal of pollutants, and low operational and maintenance costs. Plants play an important role in enhancing the WW treatment process in CW. Therefore, selection of the appropriate plant species to be grown in CW is an important criterion to ensure the success of the CW system. The performances of 5 plant species, namely, Typha (Typha spp), Dwarf Napier (Pennisetum purpureum), Guinea grass (Panicum maximum) and 2 varieties of Kenaf (Hibiscus cannabinus L) i.e. K 465/118 (K465) and Thai Kenaf grown in cattle WW were evaluated over 4 weeks. The different plant species were ranked using Typha (a widely use plant for phytoremediation) as a control based on their percentage of mortality, rate of growth of the root system, crude protein (CP) content, dry matter yield (DMY), and palatability score. The results showed that Typha had the highest score followed by Napier, K465 Kenaf, Thai Kenaf and Guinea. Based on the results of this study three plant species (Typha, Napier and K465 Kenaf) were selected for further evaluations in experiment 2.